Traditional and complementary/alternative medicine use in a South-Asian population - F Amin; N Islam; AH Gilani (Asian Pacific Journal of Health Sciences, 2015)
Traditional, complementary/alternative medicine (CAM/T) is popular in South-Asian countries, where accessibility and cost of conventional medicine is an issue. This survey explores CAM/T use in a sub-urban population in Pakistan. A validated questionnaire was used to survey 355 participants, selected by systematic sampling. Among them 63% believed in the potential of CAM/T to heal while 58% preferred CAM/T over conventional medicine, mainly because of cost-effectiveness. Around 82% had either been to a CAM/T healthcare provider or used selfhelp practices in the last one year for health and 85% said that they do not inform their physicians about CAM/T use. Females were more likely to consult a CAM/T provider for symptoms like back pain, leucorrhoea and body aches. This popularity of CAM/T in our region promotes to gain an insight into the use of CAM/T in communities for integration of CAM/T with conventional healthcare leading to cost-effective and efficient primary healthcare.